Estudo de investigação química da espécie Lippia rigida Schauer (Verbenaceae). - Oliveira, Francisco Carlos de (2012)
This paper describes the study of chemical research of the species Lippia rigida Schauer (Verbenaceae), collected in the municipality of Muncugê, Bahia. Chromatographic analysis of the ethanol extract from leaves of L. rigid allowed the isolation and characterization of flavonoid-type flavanones 3 sakuranetin, pinocembrin and naringenin 2 flavanonois 7-methyl aromadendrin and taxifolin, 1 flavone genkwanin, 3 flavonois ramnocitrin, kaempferol and quercetin. In the structural determination of secondary metabolites isolated, we used spectroscopic techniques such as infrared (IR) and hydrogen nuclear magnetic resonance (1H NMR) and carbon-13 (13C NMR), including two-dimensional techniques (COSY, HMBC and HSQC), and mass spectrometry (MS) and comparison with literature data. Although all the compounds are known in the literature, the isolation of flavonoids for the species L. rigida chemotaxonomy corroborates dispersal of this class to the genus Lippia. Moreover, the compound 7-methyl-aromadendrin, ramnocitrina, genkwanina and kaempferol are being reported for the first time for the genus, besides the more flavonoids 7-methyl-aromadendrin ramnocitrina and are being reported for the first time for the family Verbenaceae. The essential oil of Lippia rigida leaves was obtained by hydrodistillation and analyzed in GC-MS and GC-FID. The major components of the essential oil were α-humulene (42.3%) and β-caryophyllene (13,0%). The oil was subjected testing larvicidal activity against larvae in stage III of the mosquito Aedes aegypti and presented with LC50 of 138.97 ± 1.2 mg/mL. Assay of cytotoxicity activity against cell lines MDA-MB435, HCT-8 and SF-295, IC% showed 83.79, 86.80 and 79.41, respectively. The activity of inhibiting the enzyme acetylcholinesterase inhibition zone revealed with 9 mm similar to control physostigmine.